DIFFUSE TOXIC BULGE CAUSED BY CHANGES IN THYROID ACTIVITY - Salimova, Dildora Erkinovna; Haydarov , Dovudbek; Eshtemirov, Asror; Onarbayev, Abu Tohir (Educational Research in Universal Sciences, 2024)
Diffuse toxic bull disease (tyreotoxicosis, tyreotoxic Bull) is considered an endocrine disease and occurs as a result of an excessive increase in the secretion of thyroid hormones, it is accompanied by severe disorders in various organs and systems. This disease is a disease that is given little attention among the people, but is accompanied by severe complications, and it is important to dwell on it separately.